Al: A Boon to Social Media Marketing - Prince Mekhya; Hemangi Prajapati; Jignesh Vidani (Journal of Advanced Research in Economics and Business Management, 2024)
The integration of Artificial Intelligence (AI) has revolutionized the landscape of digital marketing, particularly in the realm of Social Media Marketing (SMM). This report delves into the profound impact of AI technology on the effectiveness and efficiency of social media marketing strategies. It scrutinizes various applications of AI in SMM, including chatbots, sentiment analysis, personalized content recommendations, and predictive analytics. The paper begins by outlining the current state of social media marketing and the challenges marketers face in engaging target consumers amidst the abundance of digital content. It then explores how AI can address these challenges by automating processes. Through an extensive literature review and case studies, the report illustrates real-world applications of AI in SMM, highlighting success stories and identifying areas for further development. Additionally, it examines ethical considerations surrounding privacy, bias, and transparency inherent in AI-driven marketing. Methodologies for research design, data collection, and analysis are detailed to evaluate the impact of AI on SMM efficacy. Utilizing data from surveys, interviews, and performance metrics, both quantitative and qualitative aspects of AI integration in SMM are elucidated. In the conclusion, key findings are summarized, emphasizing the benefits of AI utilization in social media marketing and offering recommendations for companies and marketers seeking to leverage these technologies fully. The article concludes by discussing the future trajectory of AI in SMM, considering potential advancements, challenges, and opportunities. This study contributes to the growing body of research on AI and marketing, furnishing practitioners, researchers, and business professionals with valuable insights for navigating the evolving social landscape in the digital age.